2016
DOI: 10.15447/sfews.2016v14iss1art2
|View full text |Cite
|
Sign up to set email alerts
|

Abundance Trends, Distribution, and Habitat Associations of the Invasive Mississippi Silverside (Menidia audens) in the Sacramento–San Joaquin Delta, California USA

Abstract: Although many alien fish species have colonized the Sacramento-San Joaquin Delta (Delta), few are as pervasive and abundant as Mississippi Silversides (Menidia audens). Moreover, Mississippi Silversides are hypothesized to be an intra-guild predator of the endangered Delta Smelt (Hypomesus transpacificus). Because of their prevalence in the Delta and potential predation on Delta Smelt, Mississippi Silversides may have far-reaching effects on both the aquatic ecosystem and conservation management policies of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…This association indicates that the recent proliferation of invasive macrophytes in the Delta [22,23] directly facilitated the increase of Centrarchid species. By contrast, increase in Mississippi Silversides may be driven more by the high frequency of drought years since the late 2000s based on their close association with low flow periods [25]. …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This association indicates that the recent proliferation of invasive macrophytes in the Delta [22,23] directly facilitated the increase of Centrarchid species. By contrast, increase in Mississippi Silversides may be driven more by the high frequency of drought years since the late 2000s based on their close association with low flow periods [25]. …”
Section: Discussionmentioning
confidence: 99%
“…We also found that interannual variation in the littoral fish community composition largely followed a pattern of simple progression through time over the study period, though year-to-year variability in freshwater inflow seem to play a substantial role as well. Notably, biomass per volume has also doubled over the study period, largely driven by a handful of species from the Mississippi drainage that are now widespread in the Delta [25,33]. With sea level rise and land subsidence continuing to be an issue in many Delta islands, the Delta is likely to change from the current system of tidal freshwater channels to a more diverse area consisting of flooded islands and shallow open water [37].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations